BARRIERS TO CAREER ADVANCEMENT OF FEMALE JOURNALISTS IN INDONESIA - Andina Dian Dwifatma (al-Balagh : Jurnal Dakwah dan Komunikasi, 2021)
than their female counterparts due to the heavy fieldwork and irregular working hours. Determining whether this assumption remains relevant, this study maps the proportion of female and male journalists in ten Indonesian mass media organizations while also exploring the factors that contribute to the condition.This research applies quantitative and qualitative mixed methods, involving journalists in 10 media (n = 811) at both the reporter and managerial levels, and a focused-group discussion (FGD) with 14 female editors. At the reporter level, there are 64% male and 36% female journalists. At the managerial level, the figures change to 77% (men) and 23% (women). The three factors that hinder the career of female journalists are a double burden (career and household), mental barriers, and ‘masculine’ office politics.